2022
DOI: 10.1177/14777606221136148
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aging and automotive oil effects on the performance of electron beam irradiated styrene butadiene rubber/waste and microwave devulcanized rubber blends

Abstract: Replacement of virgin polymer with its waste become one of the special technique that capture the efforts of many researchers and industrialists alike. In this context, this work discussed the partial replacement of waste tire rubber (WR) and microwave devulcanized rubber (DWR) at different ratios on the properties of virgin styrene butadiene rubber (SBR) as one of the most essential components of synthetic rubber in the tire production. Fixed percent of tetramethylthiuram disulfide and spindle oil were added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…6 shows typical stress–strain curves of pure r-HDPE and r-HDPE + x % Ilm composite sheets with varying concentrations determined at room temperature and a constant loading rate (500 mm min −1 ). 24,25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 shows typical stress–strain curves of pure r-HDPE and r-HDPE + x % Ilm composite sheets with varying concentrations determined at room temperature and a constant loading rate (500 mm min −1 ). 24,25…”
Section: Resultsmentioning
confidence: 99%
“…6 shows typical stress-strain curves of pure r-HDPE and r-HDPE + x% Ilm composite sheets with varying concentrations determined at room temperature and a constant loading rate (500 mm min −1 ). 24,25 To explore the inuence of dopant ilmenite concentration on the mechanical characteristics of r-HDPE, the tensile strength (MPa), elongation at break percent, and Young's modulus (MPa) of r-HDPE + x% Ilm composite sheets were investigated (Fig. 7).…”
Section: Mechanical Properties Of R-hdpe + X% Ilm Composite Sheetsmentioning
confidence: 99%
“…Furthermore, the peak of the C-H stretching vibration at 2849 and 2919 cm À1 does not show differences between an unirradiated and irradiated WPVC/ZnB (M) significantly that the hydrocarbon backbone is not degraded by EB-irradiation. 15 16 Also, WPVC filled with zinc borate using the melting mixing method displays several peaks at 2 thetas 17.7, 18.0, 20.5, 21.7, 22.5, 23.7, 24.1, 25.8, 27.5, 28.6, 30.2, 30.5, 30.7, 32.8, 35.9, 36.6, and 42.9°r espectively, those characteristic spectra of 2 ZnO•3B 2 O 3 •3.5 H 2 O. 17 It was observed that peaks around 2 thetas 18.7 and 25.0 were less intense in comparison with those that represent the pristine WPVC because the addition of zinc borate decreases the crystalline phase on WPVC.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the peak of the C–H stretching vibration at 2849 and 2919 cm −1 does not show differences between an unirradiated and irradiated WPVC/ZnB (M) significantly that the hydrocarbon backbone is not degraded by EB-irradiation. 15…”
Section: Resultsmentioning
confidence: 99%
“…There are many methods to improve the performance of rubber, such as modification in the synthesis and processing progress, blending with plastic and other rubbers, 5 adding additives 6–8 and nanofillers 9–11 . Among the methods, the application of nanofillers in rubber has received widespread attention.…”
Section: Introductionmentioning
confidence: 99%